(untitled) (Comprehensive Journal of Science, 2026)
Cutaneous leishmaniasis (CL) is a neglected tropical disease with significant epidemiological importance in North Africa. This study provides a comprehensive epidemiological and statistical analysis of CL cases in Tawergha, Libya, between August 2006 and April 2007. A total of 1,433 cases were analyzed using SPSS (v25). Descriptive, inferential, and multivariate analyses were performed. A significant seasonal variation was observed (ANOVA, p = 0.003), with a peak in November. Spatial clustering was highly significant (χ² = 312.6, p < 0.001), particularly in Al-Karama (44%). Logistic regression identified age (OR = 2.1, 95% CI: 1.5–2.9) and male gender (OR = 1.3, 95% CI: 1.05–1.6) as significant risk factors. The findings confirm that CL transmission in Tawergha is influenced by environmental and demographic determinants. Targeted control strategies are urgently required.